Pyometra in the postpartum: a forgotten complication - Choudhary, Rana A.; Ganla, Kedar N.; Desai, Kavita N.; Vora, Priyanka H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
We report a case of 37 years old women who conceived after in vitro fertilization (IVF). Her antenatal course was uneventful. On delivery there was placenta acreta. She later presented in the postpartum period with pyometra. She was managed with conservative treatment. We believe that the placental bed sutures and the sloughing placenta could have led to sterile pyometra in this patient. This rare but important complication need to be kept in mind specially in high risk women with thin endometrium, h/o IVF, cervical encerclage, and placenta acreta.